Implementation of Active Creative Effective and Fun Learning (PAKEM) in Class VII Islamic Education Subjects in Jetis Ponorogo N 1 Middle School Academic Year 2018-2019 - Miftahul Ulum; Gatot Handoko (Educan : Jurnal Pendidikan Islam, 2019)
Problems that arise in the learning of Islamic education to date are unpleasant learning situations. Both from the aspect of the teacher who is less ableto integrate between Islamic religious education material with other learningmaterials so that the learning atmosphere tends to be monotonous.The other aspects,relating to curriculum, learning strategies and materials for teaching Islamic religionare lacking. Researcher in this article do not want to show the causes of problemsthat occur in the learning of Islamic religious education, but rather focus theirresearch on the application of the Active creative effective and fun learning(PAKEM) in Islamic religious education. And it is expected that readers can accessaccurate knowledge about the aspects used in this study and can answer usingqualitative descriptive research methods. The general assumptions in this study donot use hypotheses (non hypothesis). The research method used by collecting datausing three types, namely; observation, interviews and documents.Theimplementation of Active creative effective and fun learning (PAKEM) in IslamicEducation Class VII in SMP 1 Jetis Ponorogo is well underway. In this case theresearcher looks at the conditions of learning where the teacher always startslearning with passionate greetings, then the method used in explaining the lessonthe teacher always complements or gives the real examples in students' daily lives.The strategies used by the teacher at the time of learning vary greatly at eachmeeting.